Estimasi Jejak Karbon dari Aktivitas Kampus Universitas Batanghari - Monik Kasman; Anggrika Riyanti; Novia Rezki Apriani (Jurnal Daur Lingkungan, 2020)
Every individual or agency activity will generate greenhouse gas emissions which could be countable and expressed as equivalent to carbon dioxide. One of the activities that produce carbon emissions is activities carried out on the campus, one of which is  Batanghari University. Batanghari University consists of 5 faculties, namely the Faculty of Teacher Training and Science, Faculty of Law, Faculty of Economics, Faculty of Engineering and Faculty of Agriculture with a total population of Batanghari University of 5,582 people including 5,278 students, 210 lecturers and 94 education staff. This study aims to analyze the amount of carbon emissions generated from activities of the Batanghari University and to compare the percentage of total carbon emissions produced from each scope. Calculation of carbon emissions using the method of The Greenhouse Gas Protocol (GHG Protocol), by dividing it into 3 scopes, including calculating the carbon footprint from transportation activities, emission form the used of gas, and emissions from electricity used and the used of paper. Carbon dioxide (CO2) emissions calculated by using the IPCC (International Panel On Climate Change) method. The results showed that the total carbon footprint produced at the Batanghari University for 6 months was 790.24 ton.CO2-eq. The distribution of emissions based on the scope as follows : scope 1 activity of electricity consumption was 162,705 ton.CO2-eq; scope 2 activities of using LPG was 0.609 ton.CO2-eq; and the scope 3 transportation activities of lecturers, students and education staff was 625.91 ton.CO2 -eq and paper usage activity are 1.0247 ton.CO2-eq. The largest carbon footprint was generated from transportation activities at 79.2% and the smallest was the use of LPG at 0.07%.